2021
DOI: 10.1016/j.dcn.2021.100996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal opioid exposure on functional networks in infancy

Abstract: Prenatal opioid exposure has been linked to altered neurodevelopment and visual problems such as strabismus and nystagmus. The neural substrate underlying these alterations is unclear. Resting-state functional connectivity MRI (rsfMRI) is an advanced and well-established technique to evaluate brain networks. Few studies have examined the effects of prenatal opioid exposure on resting-state network connectivity in infancy. In this pilot study, we characterized network connectivity in opioid-exposed infants (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
(93 reference statements)
0
17
1
Order By: Relevance
“…To date, ours is the largest cohort study focused on infants with POE. While Merhar et al also studied global brain networks in infants with POE, and their results suggest correlations of brain connectivity with Finnegan score, we did not find any such correlation in our study, which is likely due to the differences in methodology, as we used the CAP method for brain network assessment after controlling for gestational age and sex ( 27 ). Additionally, we also identified alterations in infant brain resting state functional network connectivity associated with maternal psychological factors.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…To date, ours is the largest cohort study focused on infants with POE. While Merhar et al also studied global brain networks in infants with POE, and their results suggest correlations of brain connectivity with Finnegan score, we did not find any such correlation in our study, which is likely due to the differences in methodology, as we used the CAP method for brain network assessment after controlling for gestational age and sex ( 27 ). Additionally, we also identified alterations in infant brain resting state functional network connectivity associated with maternal psychological factors.…”
Section: Discussioncontrasting
confidence: 89%
“…There have been a few recent small cohort studies showing alterations in brain resting state functional connectivity in infants with prenatal opioid exposure ( 27 , 28 ). To date, ours is the largest cohort study focused on infants with POE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that the brains of POE infants exhibited smaller network volumes, particularly in the primary visual network, and different network topologies from controls, particularly in visual and executive control networks. 28 In addition, Radhakrishnan et al 29 reported significant differences in connectivity between an amygdala seed to several cortical regions in POE infants. While these studies revealed potential neural FC alterations in POE infants, they are largely based on a static FC matrix calculated using the entire rs-fMRI scan.…”
Section: Introductionmentioning
confidence: 99%